Peer-Student-Taught Clinical Transition Session: Medical Students Entering the Clinical Clerkships - James Reinhart; Grum Cyril; Robert Stansfield (Association of American Medical Colleges, 2009)
Abstract This resource presents a short transition session for medical students entering the third-year clinical clerkships and features small-group teaching by clinically experienced near-peer medical students. The goal of this course is to supplement the traditional clinical orientation with experience-based training from peer-students, as well as to provide teaching experience to these clinically experienced peer-students. The 2-hour session consists of simulated cases specific to the beginning rotation of each new clinical student, including practice with daily progress note writing and oral presentations, question-and-answer time, and an overview of basic useful skills such as reading patient flowcharts and accessing laboratory and study results. The documents include a narrative description of the course, instructions and recruitment materials for near-peer teachers, example cases for the clinical clerkships, and survey assessments used to determine the effectiveness of the course and to plan future improvements. Average comfort level with various clinical responsibilities, as assessed by self-assessment surveys using a 5-point Likert scale, increased from 1.9 before the session to 3.1 immediately following the session. The biggest improvements were seen in vitals/chart review and progress note writing skills. Most of the survey respondents felt the session was valuable or extremely valuable at reducing first-day anxiety for their first clerkship, and practically all felt it should become a standard part of third-year orientation.